Relationship between Savings and Economic Growth in Cote d'Ivoire - Keho, Yaya (International Journal of Economics and Financial Issues, 2020)
This study examines the relationship between domestic savings and economic growth in Cote d'Ivoire during the period from 1970 to 2016. The study employs the bounds testing approach to cointegration and the Granger causality test in the examination of this relationship. The results show that in the short and long run, domestic savings is positively and significantly related to economic growth. The Granger causality results favor the conventional view that savings precede and cause economic growth. The role played by domestic savings becomes crucial in supporting the economic growth of Cote d'Ivoire. Keywords: domestic savings, economic growth, causality, causality, Cote d'Ivoire. JEL Classifications: C32, E21, O40, O55 DOI: https://doi.org/10.32479/ijefi.8781